Model Konseling Kelompok Berbasis Islam Dalam Bingkai Pendekatan Humanistik Dan Kognitif-Perilaku Siswa - Adeko, Uun Adeko; Beni Azwar; Dina Hajja Ristianti; Hartini (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to analyze the effectiveness of an Islamic-based group counseling model that integrates humanistic and cognitive-behavioral approaches to help students at SMKN 4 Kepahiang manage emotions, understand self-potential, and improve behavior. The research employed a qualitative method with data collected through in-depth interviews, participatory observation, and focus group discussions (FGDs). The findings indicate that this counseling model significantly contributes to students' psychological, emotional, and spiritual development. The humanistic approach fosters an empathetic and open counseling environment, while the Islamic cognitive-behavioral approach aids students in transforming negative thought patterns into positive ones, grounded in Islamic values such as patience (sabr), trust in God (tawakkul), and self-reflection (muhasabah). Group counseling also enhances student solidarity, motivation, and self-confidence. This model is recommended as both a preventive and curative strategy for addressing students’ psychosocial issues in vocational education settings